Sodium alginate water-air composite hydrogel, and preparation method and application thereof
Patent Information
- Application Number
- CN202611107384.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]解决的技术问题:为解决现有海藻酸钠气凝胶因光吸收能力弱而需要复合光热材料、但物理共混法容易导致光热颗粒分布不均与脱落、且材料内部难以构建理想的水通道与光热区域空间分布,以及预氧化碳化后的聚丙烯腈碳纳米纤维虽然具备优良光热性能却难以与水凝胶基质稳固结合形成一体化蒸发体的技术问题,本发明提供一种海藻酸钠水-气复合凝胶及其制备方法和应用,能够将碳纳米纤维与海藻酸钠水凝胶稳固复合,并在材料内部同时实现连续光吸收网络、梯度水分传输通道及良好的结构稳定性,从而获得高效太阳能界面蒸发性能
[0016]有益效果:(1)结构稳定,抗溶胀性强:采用先造孔、后交联的策略,先通过冷冻干燥构建骨架,再通过Ca2+交联锁定该垂直结构。这种结构在蒸发过程中能保持孔道通畅,有效解决传统气凝胶因孔道不规则导致的运水能力被削弱的问题,确保水分长期稳定传输。
Smart Images

Figure CN122875154A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solar-driven water evaporation and seawater desalination technology, specifically relating to a sodium alginate water-air composite gel material, and particularly to the preparation method of the sodium alginate water-air composite gel and its application in solar interfacial evaporation seawater desalination. Background Technology
[0002] With the global water shortage becoming increasingly severe, solar-driven interfacial water evaporation technology has attracted widespread attention due to its high efficiency, greenness, and sustainability. The key to this technology lies in developing high-performance evaporation materials that simultaneously possess efficient light absorption and photothermal conversion capabilities, sufficient water supply, good thermal management performance, and excellent salt resistance and long-term stability. Sodium alginate hydrogel, with its three-dimensional hydrophilic network, can achieve efficient water transport and has self-desalination potential, thus it is widely used in the field of interfacial evaporation. However, pure sodium alginate aerogel has two main limitations in practical applications: firstly, its light absorption capacity is relatively weak, usually requiring combination with photothermal materials to achieve ideal photothermal conversion efficiency; secondly, its mechanical strength and structural stability still need to be improved in long-term aquatic environments.
[0003] Currently, most common composite methods involve physical blending, where photothermal particles such as carbon black and carbon nanotubes are directly dispersed in a sodium alginate solution and then cross-linked. While this method is simple to operate, it easily leads to uneven distribution of photothermal particles within the gel matrix, potentially causing particle detachment during use. Furthermore, it is difficult to construct an ideal spatial distribution of water channels and photothermal regions within the material, thus limiting further improvements in evaporation performance. Polyacrylonitrile nanofibers, after pre-oxidation and carbonization, can be transformed into carbon nanofibers with excellent photothermal properties. These materials exhibit outstanding light absorption and heat conversion efficiency, showing potential to become highly efficient photothermal layers. However, how to stably and rationally combine carbon nanofibers with the hydrogel matrix to form a structurally and functionally integrated evaporator remains a technical challenge. Simple physical mixing or surface coating often results in insufficient interfacial bonding, leading to delamination or detachment during long-term use, affecting the stability and lifespan of the evaporator.
[0004] Furthermore, the pore structure of sodium alginate aerogel is crucial for water transport speed. Aerogels prepared by traditional methods have relatively random and irregular pores, which may lead to decreased water supply capacity during evaporation due to pore collapse or irregularity. Directional freezing technology can prepare aerogels with vertically oriented pores, a structure that facilitates rapid water transport; however, maintaining the stability of this structure during cross-linking and subsequent use requires further optimization. This invention addresses the shortcomings of the existing technologies by proposing a solution that can stably composite carbon nanofibers with sodium alginate hydrogel, simultaneously achieving a continuous light absorption network, gradient water transport channels, and good structural stability within the material. By employing a strategy of first creating pores and then cross-linking to lock in the vertical pore structure, and then using slurry coating and in-situ secondary cross-linking to form a robust photothermal layer, the problem of uneven distribution and easy detachment of photothermal particles, as well as water supply bottlenecks caused by irregular pores, is effectively avoided. This results in a solar interface evaporation material with excellent evaporation performance, structural stability, and good salt resistance. Summary of the Invention
[0005] Technical problems solved: To address the issues that existing sodium alginate aerogels require composite photothermal materials due to their weak light absorption capacity, but physical blending methods easily lead to uneven distribution and detachment of photothermal particles, and it is difficult to construct ideal water channels and photothermal spatial distribution within the material, and that pre-oxidized and carbonized polyacrylonitrile carbon nanofibers, although possessing excellent photothermal performance, are difficult to stably combine with the hydrogel matrix to form an integrated evaporator, this invention provides a sodium alginate water-air composite gel, its preparation method, and its applications. This gel can stably composite carbon nanofibers with sodium alginate hydrogels, and simultaneously achieve a continuous light absorption network, gradient water transport channels, and good structural stability within the material, thereby obtaining highly efficient solar interface evaporation performance.
[0006] Technical Solution: A method for preparing sodium alginate water-air composite gel, comprising the following steps: Step 1, dissolving sodium alginate in water to prepare a solution with a concentration of 1 wt.% to 10 wt.%, and preparing sodium alginate aerogel with a vertically oriented pore structure by directional freezing and freeze drying; Step 2, immersing the obtained sodium alginate aerogel in a calcium chloride solution with a concentration of 5 wt.% to 15 wt.% for crosslinking, and then soaking in water to remove excess calcium ions from the surface; Step 3, dissolving polyacrylonitrile in N,N-dimethylformamide to prepare a spinning solution with a concentration of 10 wt.% to 15 wt.%, and obtaining a polyacrylonitrile nanofiber membrane by electrospinning; Step 4, subjecting the polyacrylonitrile nanofiber membrane to pre-oxidation and carbonization treatments sequentially; Step 5, grinding the carbonized polyacrylonitrile nanofiber membrane into powder and dispersing it in a solution with a concentration of 1 wt.% to 5 wt.% for crosslinking; A mixed slurry is formed in a wt.% sodium alginate solution, wherein the mass ratio of polyacrylonitrile powder to sodium alginate is 1:5 to 1:20. The mixed slurry is coated on the upper surface of the cross-linked sodium alginate aerogel, and the cross-linking of the upper sodium alginate is initiated by the diffusion of residual calcium ions in the aerogel, thus obtaining a sodium alginate water-aerogel composite gel.
[0007] In step 1, the concentration of the sodium alginate solution is 4 wt.%, the stirring time is 2 h, the stirring speed is 30000-32000 rpm, the bottom diameter of the directional freezing mold is 3 cm, and the height is 2-10 cm.
[0008] In step 2, the concentration of the calcium chloride solution is 10 wt.%, the stirring time is 5 min, the stirring speed is 1500-2000 rpm, the crosslinking time is 10 h, and the soaking time for removing excess calcium ions from the surface by soaking in water is 2 h.
[0009] In step 3, the weight-average molecular weight of the polyacrylonitrile is 149,000-151,000, and the concentration of polyacrylonitrile in the N,N-dimethylformamide solution is 13 wt.
[0010] In step 3, the electrospinning voltage is 18 kV, the liquid feed rate is 1.5-2 mL / h, the distance between the needle and the receiver is 12 cm, and the spinning time is 12 h.
[0011] In step 4, the temperature of the pre-oxidation stage is 240 ℃, and the heating rate is 5 ℃ / min; the temperature of the carbonization stage is 500 ℃, the heating rate is 5 ℃ / min, and the nitrogen flow rate is 0.1-0.2 L / min.
[0012] In step 5, the concentration of the sodium alginate solution is 2 wt.%, and the mass ratio of polyacrylonitrile powder to sodium alginate is 1:10.
[0013] In step 5, the mass ratio of the polyacrylonitrile powder to sodium alginate is 1:5, 1:15, or 1:20.
[0014] The sodium alginate water-air composite gel prepared by the above method includes a sodium alginate aerogel substrate with a vertically oriented pore structure and a sodium alginate hydrogel layer containing carbonized polyacrylonitrile powder composited on the upper surface of the aerogel.
[0015] The above-mentioned sodium alginate water-air composite gel is used in solar interfacial evaporation seawater desalination.
[0016] Beneficial effects: (1) Stable structure and strong resistance to swelling: The strategy of first creating pores and then crosslinking is adopted. First, the skeleton is constructed by freeze drying, and then Ca crosslinking is carried out. 2+ Cross-linking locks in this vertical structure. This structure keeps the pores open during evaporation, effectively solving the problem of weakened water transport capacity caused by irregular pores in traditional aerogels, and ensuring long-term stable water transport.
[0017] (2) Strong bonding of the photothermal layer: The photothermal layer is formed by slurry coating and in-situ secondary cross-linking. The carbonized PAN powder is wrapped in the surface sodium alginate hydrogel cross-linking network, which can reduce the ability required for water evaporation and form a strong interface bond with the underlying aerogel skeleton through shared cross-linking points and physical interlocking effect, avoiding the problems of delamination and peeling during long-term use.
[0018] (3) Sidewall-induced interface evaporation: The sodium alginate water-air composite gel evaporator prepared by the present invention has a height of 3cm. The sidewall is exposed to the air, which can effectively suppress the heat loss conducted to the water body and use the ambient air to maintain a relatively low temperature at the evaporation interface, thereby further improving the energy utilization efficiency and evaporation rate. The top photothermal layer can efficiently absorb and convert solar energy into heat energy. The two work together to improve the evaporation rate.
[0019] (4) Low raw material cost and environmentally friendly: Sodium alginate is widely available and has good biocompatibility; polyacrylonitrile is a common polymer with mature carbonization process, and the entire preparation process does not require complex equipment and is easy to scale up. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the preparation process of the sodium alginate water-air composite gel obtained in Example 1 of the present invention.
[0021] Figure 2 This is a scanning electron microscope image of the sodium alginate water-air composite gel prepared in Example 1 of the present invention.
[0022] Figure 3 This is a scanning electron microscope image of the lower sodium alginate aerogel in Example 1 of the present invention.
[0023] Figure 4 The images show the UV-Vis-NIR absorption spectra of the samples prepared in Example 2 and Comparative Examples 1 and 2 of this invention.
[0024] Figure 5 This is an infrared thermograph of the surface temperature change of the sodium alginate water-air composite gel prepared in this invention under light irradiation conditions.
[0025] Figure 6 This is a graph showing the mass change of the sodium alginate water-air composite gel prepared in this invention under light irradiation conditions.
[0026] Figure 7 This is a comparison chart of the evaporation rates of the samples prepared according to the present invention.
[0027] Figure 8 The evaporation rate diagram of the sodium alginate water-air composite gel prepared in Example 2 of the present invention in sodium chloride solutions of different concentrations is shown.
[0028] Figure 9 This is a comparison chart of the concentrations of various ions in water before and after desalination of the sodium alginate water-air composite gel prepared in Example 2 of the present invention.
[0029] Figure 10 This is a continuous evaporation test of the sodium alginate water-air composite gel prepared in Example 2 of the present invention.
[0030] Figure 11 The graph shows the performance test results of the sodium alginate water-air composite gel prepared in Example 2 of this invention under different light conditions. Detailed Implementation
[0031] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0033] Example 1
[0034] (1) Preparation of sodium alginate water-air composite gel:
[0035] 4 g of sodium alginate (SA) was added to 100 mL of H₂O and stirred at 30,000-32,000 rpm for 2 h to prepare a solution with a concentration of 4 wt.%. The solution was then poured into a directional freezing mold with a bottom diameter of 3 cm and a height of 10 cm and rapidly frozen in liquid nitrogen. The frozen sample was freeze-dried for 48 h to obtain an SA aerogel with a height of 3 cm.
[0036] Add 10 g CaCl2 to 100 mL H2O to prepare a solution with a concentration of 10 wt.%, and stir at 1500-2000 rpm for 5 min until the solution is homogeneous.
[0037] The SA aerogel was immersed in the aforementioned CaCl2 solution, with the crosslinking temperature set at 25 ± 2 ℃ and the relative humidity controlled at 55% ~ 65% RH. The settling time was 10-12 h (preferably 10 h). Subsequently, it was removed and soaked in deionized water for 2 h to remove excess Ca from the surface. 2+ .
[0038] 13 g of polyacrylonitrile (PAN) was added to 100 mL of N,N-dimethylformamide (DMF), and stirred at 32,000 rpm for 3 h at 80 ℃ to prepare a spinning solution with a concentration of 13 wt.%. Electrospinning was then performed for 12 h at a voltage of 18 kV, a sample injection rate of 1.5-2 mL / h, and a needle-receiver distance of 12 cm to obtain PAN nanofiber membranes.
[0039] The PAN nanofiber membrane was placed in a tube furnace and pre-oxidized to 240 °C at a heating rate of 5 °C / min. Then it was transferred to an N2 atmosphere and heated to 500 °C at the same heating rate under an N2 flow of 0.1-0.2 L / min to complete the carbonization process.
[0040] Add 2 g of SA to 100 mL of H2O and stir at 30,000-32,000 rpm for 2 h to prepare a 2 wt.% solution. Grind the carbonized PAN nanofiber membrane into powder and disperse it in a 2 wt.% sodium alginate solution at a PAN to SA mass ratio of 1:5. Coat the mixture uniformly onto the upper surface of the aerogel that has been soaked in H2O, and allow it to stand to form a hydrogel layer through ionic cross-linking, thus obtaining a sodium alginate water-aerogel composite gel.
[0041] When the mass ratio of PAN to SA is 1:5, the excessively high content of photothermal material may clog the water transport channels of the hydrogel, leading to a decrease in the evaporation rate (2.29 kg m³). -2h -1 ).
[0042] (2) Morphological observation:
[0043] Preparation process as follows Figure 1 As shown, a sodium alginate water-air composite gel was prepared, and its morphology was observed using a scanning electron microscope. Figure 2 As shown, PAN nanofibers are tightly bonded to SA hydrogel, providing reinforcement, while the vertical structure of the underlying SA aerogel allows for effective water supply.
[0044] The lower SA aerogel layer features highly regular vertically oriented channels, providing a direct, low-resistance transport path for water molecules from the bottom water body to the upper evaporation interface. This ensures a dynamic match between water supply and evaporation at high evaporation rates, preventing performance degradation due to insufficient water supply. Furthermore, the upper photothermal layer and the lower aerogel substrate form chemical bonds and physical interlocks through shared Ca²⁺ crosslinking points, resulting in a strong interfacial bond and effectively preventing peeling and failure of the photothermal layer during long-term use. In addition, the abundant hydrophilic groups (-COO₂) in the crosslinked network... - The -OH groups form a preferential hydration layer on the pore wall, which can both promote the rapid transport of water molecules and inhibit Na+. + With Cl - Crystallization occurs on the surface of the pores, thus endowing the material with excellent salt resistance. The synergistic effect of these three factors enables the composite gel to achieve a balance between efficient water supply, structural stability, and long-lasting salt resistance.
[0045] (3) Seawater desalination performance test:
[0046] Using a solar-simulated xenon lamp as the light source, the light intensity was adjusted to 1 kW m. -2 A 3 g / 100 mL sea salt aqueous solution was used to simulate seawater. Sodium alginate water-air composite gel was inserted into the center hole of EPE foam as a support, with the gel protruding 1 cm above the water surface. A beaker was used as the seawater container to construct a seawater desalination evaporation device. The device was placed on a precision balance, and the change in the container's mass during evaporation was continuously recorded. The evaporation rate calculation formula is shown below, and the test results are shown below. Figure 7 .from Figure 7 It can be seen that its evaporation rate v is 2.29 kg m -2 h -1 .
[0047]
[0048] Where dm is the mass of evaporated water, S is the area exposed to sunlight, and dt is the evaporation time.
[0049] (4) Photothermal response test:
[0050] The temperature change of the sodium alginate water-air composite gel during evaporation was recorded using an infrared imager. The test results are as follows: Figure 5 As shown, the top temperature rises to 28.7℃ in 5 minutes, indicating that the material has good photothermal properties.
[0051] Example 2
[0052] (1) Preparation of sodium alginate water-air composite gel:
[0053] 4 g of SA was added to 100 mL of H2O and stirred at 30,000-32,000 rpm for 2 h to prepare a solution with a concentration of 4 wt.%. The solution was then poured into a directional freezing mold with a bottom diameter of 3 cm and a height of 10 cm and rapidly frozen in liquid nitrogen. The frozen sample was freeze-dried for 48 h to obtain SA aerogel.
[0054] Add 10 g CaCl2 to 100 mL H2O to prepare a solution with a concentration of 10 wt.%, and stir at 1500-2000 rpm for 5 min until the solution is homogeneous.
[0055] The SA aerogel was immersed in the aforementioned CaCl2 solution, with the crosslinking temperature set at 25 ± 2 ℃ and the relative humidity controlled at 55% ~ 65% RH. The settling time was 10-12 h (preferably 10 h). Subsequently, it was removed and soaked in deionized water for 2 h to remove excess Ca from the surface. 2+ .
[0056] 13 g of PAN was added to 100 mL of DMF and stirred at 32,000 rpm for 3 h at 80 ℃ to prepare a spinning solution with a concentration of 13 wt.%. Electrospinning was performed for 12 h at a voltage of 18 kV, a sample injection rate of 1.5-2 mL / h, and a needle-receiver distance of 12 cm to obtain a PAN nanofiber membrane.
[0057] The PAN nanofiber membrane was placed in a tube furnace and pre-oxidized to 240 °C at a heating rate of 5 °C / min. Then it was transferred to an N2 atmosphere and heated to 500 °C at the same heating rate under an N2 flow of 0.1-0.2 L / min to complete the carbonization process.
[0058] Add 2 g of SA to 100 mL of H2O and stir at 30,000-32,000 rpm for 2 h to prepare a 2 wt.% solution. Grind the carbonized PAN nanofiber membrane into powder and disperse it in a 2 wt.% sodium alginate solution at a PAN to SA mass ratio of 1:10. Coat the mixture uniformly onto the upper surface of the aerogel that has been soaked in H2O, and allow it to stand to form a hydrogel layer through ionic cross-linking, thus obtaining a sodium alginate water-aerogel composite gel.
[0059] (2) Light absorption rate test:
[0060] The light absorbance of sodium alginate water-air composite gel in the 250-2500 nm range was measured using a UV / VIS / NIR spectrometer. The test results are shown in [Figure number missing]. Figure 4 Its light absorption rate is 91.3%.
[0061] (3) Seawater desalination performance test:
[0062] Using a solar-simulated xenon lamp as the light source, the light intensity was adjusted to 1 kW m. -2 A 3 g / 100 mL sea salt aqueous solution was used to simulate seawater. Sodium alginate water-air composite gel was inserted into the center hole of EPE foam as a support, and the height of the gel protruding above the water surface was adjusted to 1 cm. A beaker was used as the seawater container to construct a seawater desalination evaporation device. The above device was placed on a precision balance, and the change in the container's mass during evaporation was continuously recorded. The test results are shown below. Figure 6 and Figure 7 Its evaporation rate is 2.99 kg m³. -2 h -1 .
[0063] (4) Photothermal response test:
[0064] The temperature change of the sodium alginate water-air composite gel during evaporation was recorded using an infrared imager. The test results are as follows: Figure 5 As shown, the top temperature rises to 33.2℃ in 5 minutes, indicating that the material has good photothermal properties.
[0065] (5) Salt resistance test:
[0066] Sodium alginate water-air composite gel was applied to NaCl solutions of different concentrations to test the evaporation performance of the material in high-salinity seawater. The test results are shown below. Figure 8 The sodium alginate water-air composite gel maintained a stable evaporation rate in NaCl solutions of different concentrations. This indicates that the sodium alginate water-air composite gel can treat high-concentration brine and exhibits long-term stability.
[0067] (6) Water purification capacity test:
[0068] Detecting Na in the water obtained after desalination + K + Mg 2+ Ca 2+ The ion concentration, test results are shown in [link to results]. Figure 9 The concentrations of all ions decreased by at least two orders of magnitude. This indicates that sodium alginate water-air composite gel can effectively purify seawater.
[0069] Evaporation rates compared to Examples 1-4 Figure 7 It can be observed that as the mass ratio of PAN carbonide to SA increases from 1:5 to 1:10, the evaporation rate significantly increases, due to the enhanced photothermal conversion capability. However, when the ratio is further increased to 1:15 and 1:20, the evaporation rate decreases, possibly because excessive or insufficient photothermal material can disrupt the continuous water transport channels of the hydrogel or reduce the photothermal conversion efficiency. Therefore, the preferred mass ratio of PAN carbonide to SA is 1:10, at which point the evaporation rate reaches its maximum value of 2.99 kg m³. -2 h -1 Although Examples 1 and 3 and 4 also achieved higher evaporation effects than the comparative example, they were not as ideal as Example 2.
[0070] (7) Cyclic Evaporation Test
[0071] Sodium alginate water-air composite gel was placed in a 3.5 wt% sodium chloride solution simulating seawater. Under constant light and environmental conditions, it was continuously evaporated for 5 hours daily, then evaporation was stopped and the gel was allowed to recover naturally overnight. This cycle was repeated for a total of 10 days (50 effective evaporation hours). The daily evaporation volume was recorded, and the corresponding evaporation rate was calculated. The test results are shown below. Figure 10 The initial evaporation rate of the evaporator is approximately 3.0 kg m³. -2 h -1 It decreased slightly over the next few days, but remained at 2.3 kg m after 10 cycles. -2 h -1 The slight performance degradation can be attributed to the gradual accumulation of salt crystals on the evaporator surface, which slightly hinders interfacial water transport and light absorption processes. The results demonstrate that the SSC evaporator possesses excellent reusability and structural stability, showing promising application prospects in practical solar-driven seawater desalination applications.
[0072] (8) Tests under different light intensities
[0073] To investigate the evaporation response characteristics and energy utilization efficiency of sodium alginate water-air composite gel under different incident light power densities, this study set up gradient illumination conditions to simulate weak light (0.5 sun, i.e., 500 W / m²).-2 Standard sunlight (1 sun, 1000 W / m²) -2 ) and strong light (2 sun, 2000 W·m -2 Three typical irradiation scenarios were investigated. Under each irradiation intensity, the composite gel was placed in a 3.5 wt% NaCl solution and continuously evaporated for 5 h. The mass change of water was monitored in real time, and the corresponding evaporation rate was calculated. The test results are as follows: Figure 11 As shown.
[0074] Under 0.5 ppm sunlight, the SSC evaporator achieves an evaporation rate of 1.27 kg / m³. -2 h -1 Compared to pure seawater (0.42 kgm) -2 h -1 The evaporation rate increased by approximately 2.6 times. With increasing light intensity, the evaporation rate increased linearly, reaching 2.99 kg / m³ at 1.0 sun. -2 h -1 2.0 sun delivers 4.19 kg m -2 h -1 The positive correlation between evaporation rate and light intensity further confirms the stable photothermal response characteristics of the SSC-4 evaporator.
[0075] Example 3
[0076] 4 g of SA was added to 100 mL of H2O and stirred at 30,000-32,000 rpm for 2 h to prepare a solution with a concentration of 4 wt.%. The solution was then poured into a directional freezing mold with a bottom diameter of 3 cm and a height of 10 cm and rapidly frozen in liquid nitrogen. The frozen sample was freeze-dried for 48 h to obtain SA aerogel.
[0077] Add 10 g CaCl2 to 100 mL H2O to prepare a solution with a concentration of 10 wt.%, and stir at 1500-2000 rpm for 5 min until the solution is homogeneous.
[0078] The SA aerogel was immersed in the aforementioned CaCl2 solution, with the crosslinking temperature set at 25 ± 2 ℃ and the relative humidity controlled at 55% ~ 65% RH. The settling time was 10-12 h (preferably 10 h). Subsequently, it was removed and soaked in deionized water for 2 h to remove excess Ca from the surface. 2+ .
[0079] 13 g of PAN was added to 100 mL of DMF and stirred at 32,000 rpm for 3 h at 80 ℃ to prepare a spinning solution with a concentration of 13 wt.%. Electrospinning was performed for 12 h at a voltage of 18 kV, a sample injection rate of 1.5-2 mL / h, and a needle-receiver distance of 12 cm to obtain a PAN nanofiber membrane.
[0080] The PAN nanofiber membrane was placed in a tube furnace and pre-oxidized to 240 °C at a heating rate of 5 °C / min. Then it was transferred to an N2 atmosphere and heated to 500 °C at the same heating rate under an N2 flow of 0.1-0.2 L / min to complete the carbonization process.
[0081] Add 2 g of SA to 100 mL of H2O and stir at 30,000-32,000 rpm for 2 h to prepare a 2 wt.% solution. Grind the carbonized PAN nanofiber membrane into powder and disperse it in a 2 wt.% sodium alginate solution at a PAN to SA mass ratio of 1:15. Coat the mixture uniformly onto the upper surface of the aerogel that has been soaked in H2O, and allow it to stand to form a hydrogel layer through ionic cross-linking, thus obtaining a sodium alginate water-aerogel composite gel.
[0082] (1) Seawater desalination performance test:
[0083] Using a solar-simulated xenon lamp as the light source, the light intensity was adjusted to 1 kW m. -2 A 3 g / 100 mL sea salt aqueous solution was used to simulate seawater. Sodium alginate water-air composite gel was inserted into the center hole of EPE foam as a support, and the height of the gel protruding above the water surface was adjusted to 1 cm. A beaker was used as the seawater container to construct a seawater desalination evaporation device. The above device was placed on a precision balance, and the change in the container's mass during evaporation was continuously recorded. The test results are shown below. Figure 7 Its evaporation rate is 2.34 kg m³. -2 h -1 The evaporation rate was lower than that in Example 2.
[0084] (2) Photothermal response test:
[0085] The temperature change of the sodium alginate water-air composite gel during evaporation was recorded using an infrared imager. The test results are as follows: Figure 5 As shown, the top temperature rises to 31.2℃ in 5 minutes, indicating that the material has good photothermal properties.
[0086] Example 4
[0087] 4 g of SA was added to 100 mL of H2O and stirred at 30,000-32,000 rpm for 2 h to prepare a solution with a concentration of 4 wt.%. The solution was then poured into a directional freezing mold with a bottom diameter of 3 cm and a height of 10 cm and rapidly frozen in liquid nitrogen. The frozen sample was freeze-dried for 48 h to obtain SA aerogel.
[0088] Add 10 g CaCl2 to 100 mL H2O to prepare a solution with a concentration of 10 wt.%, and stir at 1500-2000 rpm for 5 min until the solution is homogeneous.
[0089] The SA aerogel was immersed in the aforementioned CaCl2 solution, with the crosslinking temperature set at 25 ± 2 ℃ and the relative humidity controlled at 55% ~ 65% RH. The settling time was 10-12 h (preferably 10 h). Subsequently, it was removed and soaked in deionized water for 2 h to remove excess Ca from the surface. 2+ .
[0090] 13 g of PAN was added to 100 mL of DMF and stirred at 32,000 rpm for 3 h at 80 ℃ to prepare a spinning solution with a concentration of 13 wt.%. Electrospinning was performed for 12 h at a voltage of 18 kV, a sample injection rate of 1.5-2 mL / h, and a needle-receiver distance of 12 cm to obtain a PAN nanofiber membrane.
[0091] The PAN nanofiber membrane was placed in a tube furnace and pre-oxidized to 240 °C at a heating rate of 5 °C / min. Then it was transferred to an N2 atmosphere and heated to 500 °C at the same heating rate under an N2 flow of 0.1-0.2 L / min to complete the carbonization process.
[0092] Add 2 g of SA to 100 mL of H2O and stir at 30,000-32,000 rpm for 2 h to prepare a 2 wt.% solution. Grind the carbonized PAN nanofiber membrane into powder and disperse it in a 2 wt.% sodium alginate solution at a PAN to SA mass ratio of 1:20. Coat the mixture uniformly onto the upper surface of the H2O-soaked aerogel and allow it to stand to form a hydrogel layer through ionic cross-linking, thus obtaining a sodium alginate water-aerogel composite gel.
[0093] (1) Seawater desalination performance test:
[0094] Using a solar-simulated xenon lamp as the light source, the light intensity was adjusted to 1 kW m. -2A 3 g / 100 mL sea salt aqueous solution was used to simulate seawater. Sodium alginate water-air composite gel was inserted into the center hole of EPE foam as a support, and the height of the gel protruding above the water surface was adjusted to 1 cm. A beaker was used as the seawater container to construct a seawater desalination evaporation device. The above device was placed on a precision balance, and the change in the container's mass during evaporation was continuously recorded. The test results are shown below. Figure 7 Its evaporation rate is 2.85 kg m³. -2 h -1 The evaporation rate was lower than that in Example 2.
[0095] (2) Photothermal response test:
[0096] The temperature change of the sodium alginate water-air composite gel during evaporation was recorded using an infrared imager. The test results are as follows: Figure 5 As shown, the top temperature rises to 32.1℃ in 5 minutes, indicating that the material has good photothermal properties.
[0097] Comparative Example 1
[0098] 4 g of SA was added to 100 mL of H2O and stirred at 30,000-32,000 rpm for 2 h to prepare a solution with a concentration of 4 wt.%. The solution was then poured into a directional freezing mold with a bottom diameter of 3 cm and a height of 10 cm and rapidly frozen in liquid nitrogen. The frozen sample was freeze-dried for 48 h to obtain SA aerogel.
[0099] Add 10 g CaCl2 to 100 mL H2O to prepare a solution with a concentration of 10 wt.%, and stir at 1500-2000 rpm for 5 min until the solution is homogeneous.
[0100] The SA aerogel was immersed in the aforementioned CaCl2 solution, with the crosslinking temperature set at 25 ± 2 ℃ and the relative humidity controlled at 55% ~ 65% RH. The settling time was 10-12 h (preferably 10 h). Subsequently, it was removed and soaked in deionized water for 2 h to remove excess Ca from the surface. 2+ .
[0101] (1) Seawater desalination performance test:
[0102] Using a solar-simulated xenon lamp as the light source, the light intensity was adjusted to 1 kW m. -2A 3 g / 100 mL sea salt aqueous solution was used to simulate seawater. Sodium alginate water-air composite gel was inserted into the center hole of EPE foam as a support, and the height of the gel protruding above the water surface was adjusted to 1 cm. A beaker was used as the seawater container to construct a seawater desalination evaporation device. The above device was placed on a precision balance, and the change in the container's mass during evaporation was continuously recorded. The test results are shown below. Figure 7 Its evaporation rate is 1.91 kg m³. -2 h -1 The evaporation rate was lower than that in Example 2.
[0103] (2) Light absorption rate test:
[0104] The light absorbance of sodium alginate water-air composite gel in the 250-2500 nm range was measured using a UV / VIS / NIR spectrometer. The test results are shown in [Figure number missing]. Figure 4 Its light absorption rate is 39.8%.
[0105] Comparative Example 2
[0106] 4 g of SA was added to 100 mL of H2O and stirred at 30,000-32,000 rpm for 2 h to prepare a solution with a concentration of 4 wt.%. The solution was then poured into a directional freezing mold with a bottom diameter of 3 cm and a height of 10 cm and rapidly frozen in liquid nitrogen. The frozen sample was freeze-dried for 48 h to obtain SA aerogel.
[0107] Add 10 g CaCl2 to 100 mL H2O to prepare a solution with a concentration of 10 wt.%, and stir at 1500-2000 rpm for 5 min until the solution is homogeneous.
[0108] The SA aerogel was immersed in the aforementioned CaCl2 solution, with the crosslinking temperature set at 25 ± 2 ℃ and the relative humidity controlled at 55% ~ 65% RH. The settling time was 10-12 h (preferably 10 h). Subsequently, it was removed and soaked in deionized water for 2 h to remove excess Ca from the surface. 2+ .
[0109] Add 2 g of SA to 100 mL of H2O and stir at 30,000-32,000 rpm for 2 h to prepare a solution with a concentration of 2 wt.%. Coat the upper surface of the aerogel soaked in H2O with the 2 wt.% SA solution uniformly, and allow it to stand to form a hydrogel layer through ionic cross-linking, ultimately obtaining a sodium alginate water-aerogel composite gel.
[0110] (1) Seawater desalination performance test:
[0111] Using a solar-simulated xenon lamp as the light source, the light intensity was adjusted to 1 kW m. -2 A 3 g / 100 mL sea salt aqueous solution was used to simulate seawater. Sodium alginate water-air composite gel was inserted into the center hole of EPE foam as a support, and the height of the gel protruding above the water surface was adjusted to 1 cm. A beaker was used as the seawater container to construct a seawater desalination evaporation device. The above device was placed on a precision balance, and the change in the container's mass during evaporation was continuously recorded. The test results are shown below. Figure 7 Its evaporation rate is 2.0 kg m³. -2 h -1 The evaporation rate was lower than that in Example 2.
[0112] (2) Light absorption rate test:
[0113] The light absorbance of sodium alginate water-air composite gel in the 250-2500 nm range was measured using a UV / VIS / NIR spectrometer. The test results are shown in [Figure number missing]. Figure 4 Its light absorption rate is 77.2%.
[0114] Comparative Example 3
[0115] Add 4 g of SA to 100 mL of H2O and stir at 30,000-32,000 rpm for 2 h to prepare a solution with a concentration of 4 wt.%. Then, disperse the carbonized PAN powder in a 2 wt.% sodium alginate solution at a PAN to SA mass ratio of 1:5.
[0116] The mixed solution was poured into a directional freezing mold with a bottom diameter of 3 cm and a height of 10 cm, and then rapidly frozen in liquid nitrogen. The frozen sample was freeze-dried for 48 h to obtain SA aerogel.
[0117] Add 10 g CaCl2 to 100 mL H2O to prepare a solution with a concentration of 10 wt.%, and stir at 1500-2000 rpm for 5 min until the solution is homogeneous.
[0118] The SA aerogel was immersed in the aforementioned CaCl2 solution, with the crosslinking temperature set at 25 ± 2 ℃ and the relative humidity controlled at 55% ~ 65% RH. The settling time was 10-12 h (preferably 10 h). Subsequently, it was removed and soaked in deionized water for 2 h to remove excess Ca from the surface. 2+ .
[0119] (1) Seawater desalination performance test:
[0120] Using a solar-simulated xenon lamp as the light source, the light intensity was adjusted to 1 kW m. -2A 3 g / 100 mL sea salt aqueous solution was used to simulate seawater. Sodium alginate water-air composite gel was inserted into the center hole of EPE foam as a support, and the height of the gel protruding above the water surface was adjusted to 1 cm. A beaker was used as the seawater container to construct a seawater desalination evaporation device. The above device was placed on a precision balance, and the change in the container's mass during evaporation was continuously recorded. The test results are shown below. Figure 7 Its evaporation rate is 2.81 kg m³. -2 h -1 The evaporation rate was lower than that in Example 2.
[0121] The above examples are merely illustrative of the technical concept and features of the present invention, intended to enable those skilled in the art to understand the content of the invention and implement it accordingly, and should not be construed as limiting the scope of protection of the present invention. All equivalent transformations or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing sodium alginate water-air composite gel, characterized in that, The process includes the following steps: Step 1, dissolving sodium alginate in water to prepare a solution with a concentration of 1 wt.%–10 wt.%, and preparing sodium alginate aerogel with a vertically oriented pore structure by directional freezing and freeze-drying; Step 2, immersing the obtained sodium alginate aerogel in a calcium chloride solution with a concentration of 5 wt.%–15 wt.% for cross-linking, and then soaking in water to remove excess calcium ions from the surface; Step 3, dissolving polyacrylonitrile in N,N-dimethylformamide to prepare a spinning solution with a concentration of 10 wt.%–15 wt.%, and obtaining a polyacrylonitrile nanofiber membrane by electrospinning; Step 4, subjecting the polyacrylonitrile nanofiber membrane to pre-oxidation and carbonization treatments sequentially; Step 5, grinding the carbonized polyacrylonitrile nanofiber membrane into powder and dispersing it in a solution with a concentration of 1 wt.%–5 wt.%. A mixed slurry is formed in a wt.% sodium alginate solution, wherein the mass ratio of polyacrylonitrile powder to sodium alginate is 1:5 to 1:
20. The mixed slurry is coated on the upper surface of the cross-linked sodium alginate aerogel, and the cross-linking of the upper sodium alginate is initiated by the diffusion of residual calcium ions in the aerogel, thus obtaining a sodium alginate water-aerogel composite gel.
2. The preparation method according to claim 1, characterized in that, In step 1, the concentration of the sodium alginate solution is 4 wt.%, the stirring time is 2 h, the stirring speed is 30000-32000 rpm, the bottom diameter of the directional freezing mold is 3 cm, and the height is 2-10 cm.
3. The preparation method according to claim 1, characterized in that, In step 2, the concentration of the calcium chloride solution is 10 wt.%, the stirring time is 5 min, the stirring speed is 1500-2000 rpm, the cross-linking time is 10 h, and the soaking time for removing excess calcium ions from the surface by soaking in water is 2 h.
4. The preparation method according to claim 1, characterized in that, In step 3, the weight-average molecular weight of the polyacrylonitrile is 149,000-151,000, and the concentration of polyacrylonitrile in the N,N-dimethylformamide solution is 13 wt.
5. The preparation method according to claim 1, characterized in that, In step 3, the electrospinning voltage is 18 kV, the liquid feed rate is 1.5-2 mL / h, the distance between the needle and the receiver is 12 cm, and the spinning time is 12 h.
6. The preparation method according to claim 1, characterized in that, In step 4, the temperature of the pre-oxidation stage is 240℃, and the heating rate is 5℃ / min; the temperature of the carbonization stage is 500℃, the heating rate is 5℃ / min, and the nitrogen flow rate is 0.1-0.2 L / min.
7. The preparation method according to claim 1, characterized in that, In step 5, the concentration of the sodium alginate solution is 2 wt.%, and the mass ratio of polyacrylonitrile powder to sodium alginate is 1:
10.
8. The preparation method according to claim 1, characterized in that, In step 5, the mass ratio of the polyacrylonitrile powder to sodium alginate is 1:5, 1:15, or 1:
20.
9. The sodium alginate water-air composite gel prepared by any one of claims 1-8, characterized in that, It includes a sodium alginate aerogel substrate with a vertically oriented pore structure and a sodium alginate hydrogel layer containing carbonized polyacrylonitrile powder composited on the upper surface of the aerogel.
10. The application of the sodium alginate water-air composite gel according to claim 9 in solar interfacial evaporation seawater desalination.